Da ordem e de transgressão: a questão da hi[e]stória no festivo Ciclo da Paixão de Cristo em São João del-Rei, Minas Gerais - Ana Paula Lessa Beloni (2013)
This study presents an ethnography of the cycle of the Christs Passion in the historical center of São João del-Rei, Minas Gerais, which celebrates the Gods sacrifice for long days until the resurrection on Easter, the core mythical-mystical and theological of Catholicism. This religious multiverse has chosen to sustain, in contemporary party,elements of baroque and colonial history of the partys past that are used to make actual. So that, at first, notes dimension of pomp, luxury and exhibition. In a second moment highlights the empire of order, which shows the whole party trespasser character. Indeed, is in transgression of transgression, which the molds of the partys past are dramatized in contemporary party.